PRAKTEK MONOPOLI PELAYANAN JASA BONGKAR MUAT PETIKEMAS OLEH PT PELABUHAN INDONESIA III (PERSERO) - Nada Rania Dewi (2022)
The growing world economy is in line with increasing competition in various businesses, including in the logistics sector. PT. Pelabuhan Indonesia III (Persero), which is a BUMN in the logistics business sector which is considered to be carrying out monopolistic practices based on the KPPU's decision Number 05/KPUU-L/2018, BUMN which should be excluded from the application of the Business Competition Law, has been proven to have abused monopoly power by carrying out a full policy. stacking which causes production prices to increase and then the burden of these costs is passed on to consumers and concentrates economic power. This study aims to determine the cause of the monopoly practice carried out by natural gas managers in the logistics sector by PT Pelabuhan Indonesia III (Persero) and whether the activities carried out by PT Pelabuhan Indonesia III (Persero) are included in the exception to the application of Business Competition Law. The research method used is normative juridical, with a statutory and case approach taken from the KPPU's decision, namely Decision Number 15/KPPU-L/2018. The results of this thesis research state that PT. Pelabuhan Indonesia III (Persero) fulfills the elements of monopoly practice because it is detrimental to the public interest and cannot be excluded by Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition.